Electron transfer mediated activation of periodate by contaminants to generate 1O2 by charge-confined single-atom catalyst - Qianqian Tang; Bangxiang Wu; Xiaowen Huang; Wei Ren; Lingling Liu; Lei Tian; Ying Chen; Long-Shuai Zhang; Qing Sun; Zhibing Kang; Tianyi Ma; Jian-Ping Zou (Nature Communications)
Abstract The electron transfer process (ETP) is able to avoid the redox cycling of catalysts by capturing electrons from contaminants directly. However, the ETP usually leads to the formation of oligomers and the reduction of oxidants to anions. Herein, the charge-confined Fe single-atom catalyst (Fe/SCN) with Fe-N3S1 configuration was designed to achieve ETP-mediated contaminant activation of the oxidant by limiting the number of electrons gained by the oxidant to generate 1O2. The Fe/SCN-activate periodate (PI) system shows excellent contaminant degradation performance due to the combination of ETP and 1O2. Experiments and DFT calculations show that the Fe/SCN-PI* complex with strong oxidizing ability triggers the ETP, while the charge-confined effect allows the single-electronic activation of PI to generate 1O2. In the Fe/SCN + PI system, the 100% selectivity dechlorination of ETP and the ring-opening of 1O2 avoid the generation of oligomers and realize the transformation of large-molecule contaminants into small-molecule biodegradable products. Furthermore, the Fe/SCN + PI system shows excellent anti-interference ability and application potential. This work pioneers the generation of active species using ETP’s electron to activate oxidants, which provides a perspective on the design of single-atom catalysts via the charge-confined effect.